ЗАДАЧНИЙ ПІДХІД В ПЕДАГОГІЧНОМУ ПРОЦЕСІ - ОСНОВА АКТИВІЗАЦІЇ ПРОФЕСІЙНОЇ ПОЗИЦІЇ СТУДЕНТІВ (Педагогіка вищої та середньої школи, 2004)
The author determined the essence of active professional position, the structure of responsibility and it’s contents. In the research work the totality of pedagogical conditions providing the efficiency of pedagogical training in the process of formation of active professional position of the future teachers has been proved by the means of experiments.